Ruslands identitet og forhold til Vesten - Splidsboel Hansen, Flemming (Politik, 2010)
Arguably one of the most remarkable developments in Russian political life in the 2000’s, the formulation by leading politicians of a new national identity based inter alia on distrust of the West has given a large part of the Russian population a clearer understanding of who they are. As such, it has increased their ontological security, that is, their sense of existence now seen as a fundamental need for groups also. This is an unfortunate development as it increases tension in Russia’s relationship with the West. The Russian population may, however, be reluctant to move away from this new identity as this would re-open the question of „who are we?“ and thus cause their ontological security to be reduced. The challenge for the West will be to make the Russian population feel comfortable with an identity that is based on Western values and on thus on trust of the West.